MENGOPTIMALKAN KEMAMPUAN FISIK MOTORIK ANAK USIA 3-4 TAHUN MELALUI KEGIATAN BERMAIN LEMPAR TANGKAP BOLA - Sumiyati Sumiyati (JCE (Journal of Childhood Education), 2017)
The development of motor functions is one of the dimensions of early childhood development that is important to note among other development dimensions. This is a fundamental part of the child's need to develop muscle, brain, and nerves, which is one of the basic developments at a later stage. Therefore, this dimension needs to get appropriate stimulation in accordance with the stages of child development, so that stimulation is given with the right portion. One of the most effective ways to develop children motor skills is through their favorite activities, such as fun and play activities. This paper tries to explain one of the fun activity alternatives that could be used to optimize the motor physical ability of children aged 3-4 years, ie through, among others, throwing ball games. It is hoped that this paper is useful for early childhood education practitioners, as well as parents in developing ways to stimulate the development of motor skills of early childhood through fun activities